TINGKAT PENGETAHUAN ORANGTUA TENTANG ASUPAN NUTRISI YANG BAIK BAGI PERTUMBUHAN DAN PERKEMBANGAN GIGI ANAK (Jurnal Kesehatan Siliwangi, 2021)
Parents knowledge is very important in underpinning the formation of attitudes and behaviors that support or do not support children's dental and oral health. Teeth for a child are very important in the process of growth and development of children. Nutrition and dental and oral health have a close relationship, especially in children who have a growth and development phase. Good and proper nutrition is important to support dental and oral health. On the other hand, oral health is also important for adequate nutritional intake. Dental caries is one of the most common chronic infectious diseases in children and is closely related to nutrition. This type of research is descriptive, the purpose of this study is to determine the level of knowledge of parents about good nutrition for the growth and development of children's teeth in Class I SDN 142 Dwikora Bandung City. The number of samples in this study were 32 respondents (Sampling in this study used a total sampling technique, namely a sampling technique where the number of samples was the same as the population. The method of collecting data was obtained from the results of a questionnaire about parental knowledge about kinds of good nutrition and growth time and dental development of children. The results showed that 46.9% of respondents on average had good parental knowledge about nutrition for the growth and development of children's teeth. Meanwhile, in 56.3% parents' knowledge about the growth and development of children's teeth is still lacking.